Network perspective of embodied PM2.5 – A case study. (20th January 2017) - Wakeel, Muhammad; Yang, Siyuan; Chen, Bin; Hayat, Tasawar; Alsaedi, Ahmed; Ahmad, Bashir
Abstract: Economic growth due to social activities such as industrialization, urbanization, population growth, and transportation in countries like India is coupling with an increase in PM2.5 emissions, which are main contributors to air pollution. In this paper, the embodied PM2.5 emissions generated from economic activities in India were investigated. We quantified the PM2.5 emissions from each economic sector based on input-output analysis (IOA). Also, the control relations within these economic sectors were identified based on ecological network analysis (ENA) to determine the dominance and dependency of each sector. The results showed that 86% (4858 kt) of total PM2.5 emissions were direct and 14% (812 kt) were indirect in 2010. Furthermore, ENA-based results represented the pairwise control relationships among sectors by finding that "Sale, maintenance, and repair of motor vehicles, retail sale of fuel", "Chemicals and chemical products", "Smelting of nonmetal mineral products" and "Ordinary & special machinery & equipment" were the dominant sectors that controlled the flow of embodied PM2.5 emissions from other sectors such as "Construction", "Agriculture", "Mining and dressing", "Catering services", and "Waste manufacturing and recycling". It is suggested that ENA be adopted as a more systematic approach to uncover PM2.5 flow pattern among the economic sectors, as compared to traditional methods. Highlights: An embodied PM2.5 emission inventory framework on sectoral scale is constructed. The proportion of direct and indirect PM2.5 emissions is 7:1. Industrial sectors are the main controller of embodied PM2.5 emissions from services sectors.